Cosh Boy Based on a Play by Bruce Walker - Walker, Bruce (BFI Flipside, 2020)
A gang of juvenile delinquents tear up post-war London in Lewis Gilbert's (The Spy Who Loved Me, Alfie) shocking and energetic X-rated drama. Roy (James Kenney) is a brash, chain-smoking thug who bullies his friends (including Rene, played by a young Joan Collins) into subservience. He and his gang assault and rob people on the street, but things get increasingly dangerous when their behaviour escalates to murderous consequences. Unafraid to tackle a host of taboo subjects, "Cosh Boy" is a penetrating portrait of 1950s Britain and its simmering social tensions. One, of not the first British films to receive an 'X' certificate, this landmark classic is available on Blu-ray for the first time and is the 40th entry to the longstanding BFI Flipside catalogue. [www.amazon.co.uk]